Technical research on improving engine thermal efficiency. (September 2022) - Mu, Hongyu; Wang, Yinyan; Yang, Chuanlei; Teng, Hong; Zhao, Xingtian; Lu, Hongquan; Wang, Dechun; Hao, Shiyang; Zhang, Xiaolong; Jin, Yan
To aid in addressing global climate change and reduce automobile carbon emissions, the thermal efficiency of engines must be improved. By altering the structural design of an engine body (including the cylinder blocks and cylinder heads), a rapid combustion model with a compression ratio of 16 and a maximum tumble ratio of 3.94 was developed that improved the combustion speed. Through synergistic matching of cooled exhaust gas recirculation with lean burn technology, when the exhaust gas recirculation rate was 20% and the air-fuel ratio was 20, the effect of reducing NOx emission and knocking reached the optimum level. When an electronic water pump and dual thermostat technology were used, the temperature change at the combustion chamber wall of each cylinder was <3%, and when the engine ran at speeds of up to 2400 r/min and torque of up to 60 Nm, the coolant temperature could reach 105°C, thereby reducing both heat dissipation and friction losses. The maximum thermal efficiency of the new DHE16GDI engine developed based on the DAM16N engine model increased by approximately 4.4%, and the contents of the major pollutants NOx and CO and the total hydrocarbon content were reduced by approximately 43.1%, 34.8% and 8.3%, respectively.